1999
DOI: 10.1089/088922299310007
|View full text |Cite
|
Sign up to set email alerts
|

An HIV Type 1 Subtype A Outbreak among Injecting Drug Users in Latvia

Abstract: Local, explosive outbreaks of HIV-1 infections among intravenous drug users (IDUs) caused by closely related variants have been reported in the Ukraine and Russia since 1996. Latvia experienced the start of a similar outbreak at the end of 1997 and already at the end of 1998 IDUs constituted approximately 50% of all known HIV cases (122 of 251). To investigate the molecular epidemiology of HIV-1 variants circulating among Latvian IDUs the V3 domain of the env gene was directly sequenced from samples of seven r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…By 20 October 2003, the number of HIV-1 cases had reached 255,350, and more than 90% of the cases with known risk factors were IDUs. A similar situation has been observed in several other former Soviet Union republics such as Belarus [Lukashov et al, 1998], the Ukraine [Bobkov et al, 1997b;Novitsky et al, 1998], Kazakhstan [Bobkov et al, 2002], Moldova [Pandrea et al, 2001], Latvia [Ferdats et al, 1999], Lithuania [Liitsola et al, 1998], and Estonia [Ustina et al, 2001;Zetterberg et al, 2002].…”
Section: Introductionsupporting
confidence: 69%
“…By 20 October 2003, the number of HIV-1 cases had reached 255,350, and more than 90% of the cases with known risk factors were IDUs. A similar situation has been observed in several other former Soviet Union republics such as Belarus [Lukashov et al, 1998], the Ukraine [Bobkov et al, 1997b;Novitsky et al, 1998], Kazakhstan [Bobkov et al, 2002], Moldova [Pandrea et al, 2001], Latvia [Ferdats et al, 1999], Lithuania [Liitsola et al, 1998], and Estonia [Ustina et al, 2001;Zetterberg et al, 2002].…”
Section: Introductionsupporting
confidence: 69%
“…HIV-1 infection among IDUs has another unique characteristic: a very low genetic diversity among patients. The study of HIV outbreaks among IDUs in countries of the former Soviet Union, including Belarus, Ukraine, Kaliningrad, Latvia, and Russia, showed that the mean interpatient genetic distances in the C2-V3 region of the envelope were less than 2%, but a study from Nepal showed two components, one of low diversity (2,10,16,18,19,22,23). Meanwhile, the interpatient genetic distances among HIV-1 patients with heterosexual transmission were much higher, about 8% (3,23).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Sequences from the viruses infecting IDUs have been obtained for patients from the southern parts of the Russian Federation, Ukraine, Belarus, and Latvia. 7,9,10 All of these epidemics appear to have spread from single introductions, as indicated by the high homogeneity seen among the strains. [8][9][10] In this study, we investigated HIV diversity in the Republic of Moldova, a newly independent country of the former Soviet Union, to obtain valuable information on the driving forces behind the spread of HIV in this region.…”
Section: H IV Prevalence In Newly Independen T Countrie S Of Thementioning
confidence: 99%